2022
DOI: 10.3389/fmicb.2022.951958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amomum villosum essential oil as an additive on the chemical composition, fermentation quality, and bacterial community of paper mulberry silage

Abstract: Paper mulberry (Broussonetia papyrifera L., PM) is being used as a new type of animal protein feed to address the feed crisis. To investigate the effect of additives on the chemical composition, fermentation quality, and bacterial community of PM silage (at room temperature, 25°), paper mulberry was fermented with formic acid (FA), Amomum villosum essential oil (AVEO) and lactic acid bacteria (LAB) inoculant treatments. The results showed that fresh PM had a low water-soluble carbohydrate (WSC) content and lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The results of functional prediction for the microbial community of silages during ensiling are shown in Figure 3 . Chemoheterotrophy was the primary functional component of the microbial community in all silages, followed by fermentation, nitrate reduction, aerobic chemoheterotrophy and nitrogen respiration, which was similar to the results of Li et al (2022b) , who found that chemoheterotrophs were the primary functional components of the bacterial population in paper mulberry silage, followed by fermenters. In the early ensiling stage (7 days, Figure 3A ), the functions of chemoheterotrophy (34.56–36.05%) and fermentation (27.57–35.02%) of all silages showed little change.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of functional prediction for the microbial community of silages during ensiling are shown in Figure 3 . Chemoheterotrophy was the primary functional component of the microbial community in all silages, followed by fermentation, nitrate reduction, aerobic chemoheterotrophy and nitrogen respiration, which was similar to the results of Li et al (2022b) , who found that chemoheterotrophs were the primary functional components of the bacterial population in paper mulberry silage, followed by fermenters. In the early ensiling stage (7 days, Figure 3A ), the functions of chemoheterotrophy (34.56–36.05%) and fermentation (27.57–35.02%) of all silages showed little change.…”
Section: Resultssupporting
confidence: 88%
“…In the late ensiling stage (7 days, Figure 3B ), the 30% MS + 70% LP and 100% LP silages had a stronger capacity for fermentation than the other silages. This was because the 30% MS + 70% LP and 100% LP treatments showed increased abundances of LAB, such as Lentilactobacillus , Lactiplantibacillus , and Secundilactobacillus , and decreased abundances of Enterobacteriaceae ( Figure 1B ); the degree of fermentation was greater in silage ( Li et al, 2022b ). Furthermore, the 30% MS + 70% LP and 100% LP treatments had a weaker capacity for chloroplasts, animal parasites or symbionts and ureolysis than the other treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are comparable to those of Li et al, who discovered that chemoheterotrophy is the primary functional component of the bacterial population in paper mulberry silage, followed by fermentation. As fermentation proceeds, the increase in lactic acid bacteria in mixed silage accelerates fermentation, whereas the decrease in aerobic microorganisms and the dominance of lactic acid bacteria leads to less aerobic chemoheterotrophy [47]. The presence of more homofermentative lactic acid bacteria in the FA group resulted in a higher relative abundance of fermentation and a lower relative abundance of aerobic chemoheterotrophy than in the other groups.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the ZC and XJD groups had a higher abundance of Fructilactobacillus , attributed to the fermentation process promoting the breakdown of fructose in both alfalfa species, which led to an increased abundance of Fructilactobacillus . Studies have shown that Lactiplantibacillus and Lentilactobacillus were ideal functional bacteria after ensiling and can be used to improve silage quality ( Fu et al, 2022 ; Li et al, 2022 ). During the fermentation process, Lactiplantibacillus can inhibit the growth of Clostridium , thereby reducing the content of ammonium nitrogen in the feed, resulting in a higher fermentation quality of the silage ( Du et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%